PROTO MELAYU DAN DEUTERO MELAYU : DIALEKTIKA MIGRASI DAN PEMBENTUKAN IDENTITAS DI NUSANTARA - Yuanda Fracitilia Sudiar; Choirun Niswah; Ghea Audysa Sherly; Prima Sena Ardinata (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2026)
This article discusses the dialectic of the Malay Proto and Deutero migration as well as the formation of the identity of the Malay community in the archipelago. The background of the research is based on the importance of understanding the process of migration and cultural acculturation that shapes the social structure, language, art, and beliefs in the Indonesian archipelago. The research method used is a literature study with a descriptive qualitative approach, analyzing the sources of books, journals, and scientific publications related to anthropology, archaeology, linguistics, and the history of human migration. The results of the study show that the Malay Proto laid the foundations of an early culture with simple agrarian patterns and a family-based kinship system, while the Malay Deutero brought metal technology, maritime practices, and a wider trade network. The interaction of the two groups results in complex socio-cultural integration, language acculturation, and the formation of adaptive and plural community identities. In conclusion, Malay identity in the archipelago is the result of a synthesis of migration, interaction, and cultural acculturation that continues to develop into the modern context